Green synthesis nanoperak menggunakan ekstrak batang dadap serep (Erythrina Subumbrans (Hassk.) Merr) - Maharini, Indri; Fitrianingsih, Fitrianingsih; Utami, Diah Tri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Dadap serep stems contain secondary metabolite compounds of flavonoids, saponins, isoflavonoids, alkaloids and lectins which can act as reducing agents in the biosynthesis of nanosilver. This research aims to determine the effect of the concentration of liquid extract of dadap serep stem on the green synthesis silver nanoparticle (AgNPs) process. The aqueous extract of dadap serep stem reacted with one mM AgNO3 in a ratio of volume 1: 1 (FI), 1: 2 (FII), and 2: 1 (FIII). Characterization of AgNPs includes Surface Plasmon resonance (SPR) using UV/Vis spectrophotometer at wavelengths of 300-700 nm, particle size, and zeta potential using a particle size analyzer (PSA). The result showed that the SPR of AgNP values is 429-436 nm. AgNPs FI, II, and III particle sizes were 66.13 nm, 75.76 nm, and 75.96 nm, respectively. The PDI values below 0.5 confirmed that the distribution of nanoparticles was uniform. The most stable nanoparticle is Formula I.